Analysis of foot structure in young recreational female ballet dancers - Dadura Emilia; Truszczyńska-Baszak Aleksandra; Drzał-Grabiec Justyna; Krawczyk Katarzyna; Rachwał Maciej; Walicka-Cupryś Katarzyna (Sciendo, 2020)
Study aim: The human foot is an essential element of the locomotor system. It plays a key role in both the dynamics and the statics of the whole lower limb. The normal structure of the foot determines its mechanical function. During growth and formation of the foot structure, sport activity plays an important role.